2018
DOI: 10.1093/biolre/iox185
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects oocytes from MEHP exposure-induced meiosis defects in porcine†

Abstract: In 2011, DEHP (plasticizer) was reported to illegally be added in food and beverage products in Taiwan, which caused great concerns about food safety worldwide. DHEP has multiple toxic effects to human and animals such as endocrine disruption, cardiotoxicity, reproductive function, and development defects. However, the toxic effects of DEHP on mammalian oocyte quality are still unclear. Since MEHP is the active metabolite of DEHP in vivo, in this study we used porcine oocyte as model to explore the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 59 publications
4
32
0
Order By: Relevance
“…Thus, even a low concentration of melatonin can trigger a melatonin receptor‐dependent physiological response . Our study also revealed that melatonin concentration must approximately be 500 nmol/L to improve porcine embryo development, and previous studies have indicated that high concentrations of melatonin are also needed for porcine oocytes . Altogether, these results indicate that high concentrations of melatonin may mediate protective effects in porcine oocytes or early embryos.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, even a low concentration of melatonin can trigger a melatonin receptor‐dependent physiological response . Our study also revealed that melatonin concentration must approximately be 500 nmol/L to improve porcine embryo development, and previous studies have indicated that high concentrations of melatonin are also needed for porcine oocytes . Altogether, these results indicate that high concentrations of melatonin may mediate protective effects in porcine oocytes or early embryos.…”
Section: Discussionsupporting
confidence: 75%
“…Further, melatonin reportedly promotes oocyte maturation, fertilization, and early embryo development in various mammalian species . Moreover, it has been shown to protect against toxin‐induced oocyte quality impairment during maturation, mainly via its free radical scavenging and anti‐apoptosis activities . However, its beneficial effects on toxin‐exposed early embryos during in vitro culture and the possible mechanisms underlying such effects have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has a wide range of roles in physio-pathological functions, and is partly mediated by melatonin receptors in animals [23]. Melatonin treatment improves cumulus oophorus expansion of porcine COCs during IVM [24], and also increases the first polar body extrusion rate of the oocytes disrupted by heat stress and mono-(2-ethylhexyl) phthalate exposed in the porcine [7,25]. Melatonin participates in modulating functions of granulosa cell through melatonin receptor 2 (MT2), and also promotes cumulus expansion of COCs via MT2 in pigs [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that melatonin suppressed early apoptosis in IVM bovine oocytes. Several recent studies have shown that melatonin decreased ROS production and early apoptosis in mouse and porcine oocytes exposed to mycotoxins and toxicants and promoted oocyte maturation (Lan et al, ; Miao et al, ; M. Zhang et al, ; Y. Zhang et al, ). However, the underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%